STUDI LITERATUR: KESULITAN MEMBACA LANCAR PADA SISWA KELAS RENDAH DI SEKOLAH DASAR - Putri, Anike; Priyadi, Antonius Totok; Halidjah, Siti; Wibowo, Dwi Cahyadi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This article aims to describe the difficulties in reading fluency among lower-grade elementary school students through a literature review. The study employed a literature review method by analyzing 10 scientific articles obtained through a selection process from Google Scholar based on their relevance to the research topic. The data analysis technique used was content analysis to identify, categorize, and interpret the main findings from the analyzed articles. The results of the review indicate that reading difficulties among lower-grade students are a dominant issue and appear in almost all aspects of early reading skills. These difficulties include incomplete recognition of letters, inability to distinguish letter sounds, weak spelling ability, difficulty reading syllables, words, and sentences, as well as low reading fluency and reading comprehension. These findings indicate that the reading fluency of lower-grade students still requires serious attention through appropriate instructional strategies to support the development of students’ basic literacy skills in elementary school.